Conditional Disorder in Small Heat-shock Proteins. Issue 9 (17th April 2020) - Alderson, T. Reid; Ying, Jinfa; Bax, Ad; Benesch, Justin L.P.; Baldwin, Andrew J.
Abstract: Small heat-shock proteins (sHSPs) are molecular chaperones that respond to cellular stresses to combat protein aggregation. HSP27 is a critical human sHSP that forms large, dynamic oligomers whose quaternary structures and chaperone activities depend on environmental factors. Upon exposure to cellular stresses, such as heat shock or acidosis, HSP27 oligomers can dissociate into dimers and monomers, which leads to significantly enhanced chaperone activity. The structured core of the protein, the α-crystallin domain (ACD), forms dimers and can prevent the aggregation of substrate proteins to a similar degree as the full-length protein. When the ACD dimer dissociates into monomers, it partially unfolds and exhibits enhanced activity. Here, we used solution-state NMR spectroscopy to characterize the structure and dynamics of the HSP27 ACD monomer. Web show that the monomer is stabilized at low pH and that its backbone chemical shifts, 15 N relaxation rates, and 1 H– 15 N residual dipolar couplings suggest structural changes and rapid motions in the region responsible for dimerization. By analyzing the solvent accessible and buried surface areas of sHSP structures in the context of a database of dimers that are known to dissociate into disordered monomers, we predict that ACD dimers from sHSPs across all kingdoms of life may partially unfold upon dissociation. We propose a general model in which conditional disorder—the partial unfolding of ACDs upon monomerization—is a common mechanism for sHSP activity. Graphical abstract: Image 1 Highlights: NMR provides insight into the partial unfolding of α-crystallin domain monomers. 15 N relaxation and residual dipolar couplings point to extensive backbone motions in the monomer. Large scale structural bioinformatics predict that α-crystallin domain monomers from other small heat-shock proteins also partially unfold.